STIMULASI PENGENALAN ANGKA MELALUI MEDIA PEMBELAJARAN SMART BOARD FOR KIDS - Kristin Anggraini; Anita Roslina Simanjuntak; Sindy Anugerah Wati; Regina Christine Takumansang (Jurnal Abdimas Bina Bangsa, 2024)
The aim of this community service (Abdimas) activity is to introduce numbers through the Smart Board for Kids learning media. The partners in this community service activity are TK Indriyasana VII which is part of the Dharma Ibu Surabaya Foundation which is located on Jl. Dukuh Kupang XXX/51 Surabaya. The Abdimas subjects this time are 10 students currently sitting in Kindergarten A. The implementation of this community service activity was carried out for 2 months and consisted of 2 stages, namely the media introduction stage and the media use stage. In stage 1, the author introduces the Smart Board for Kids learning media to children, then in stage 2 the children are asked to play games using the Smart Board for Kids and show excellent number recognition. In conclusion, the Smart Board for kids learning media can improve number recognition in early childhood